2018
DOI: 10.1128/mbio.02379-17
|View full text |Cite
|
Sign up to set email alerts
|

IgG Responses to Porins and Lipopolysaccharide within an Outer Membrane-Based Vaccine against NontyphoidalSalmonellaDevelop at Discordant Rates

Abstract: Antibodies acquired after vaccination or natural infection with Gram-negative bacteria, such as invasive Salmonella enterica serovar Typhimurium, can protect against disease. Immunization with naturally shed outer membrane vesicles from Gram-negative bacteria is being studied for its potential to protect against many infections, since antigens within vesicles maintain their natural conformation and orientation. Shedding can be enhanced through genetic modification, and the resulting particles, generalized modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 63 publications
2
30
0
1
Order By: Relevance
“…An important and surprising implication of our results is that despite only a single Fab being able to access the LPS channel, it appears to be sufficient to promote complement-dependent killing. This conclusion is consistent with the experimental evidence showing similar binding of anti-STmOmpD IgG to WT or O-Agdeficient STm and that bacterial outer-membrane vesicle vaccines derived from bacteria lacking O-Ag can offer protection 27 . This could indicate that it is not necessary to have both arms of an antibody bound to a target antigen for it to be protective.…”
Section: Articlesupporting
confidence: 91%
“…An important and surprising implication of our results is that despite only a single Fab being able to access the LPS channel, it appears to be sufficient to promote complement-dependent killing. This conclusion is consistent with the experimental evidence showing similar binding of anti-STmOmpD IgG to WT or O-Agdeficient STm and that bacterial outer-membrane vesicle vaccines derived from bacteria lacking O-Ag can offer protection 27 . This could indicate that it is not necessary to have both arms of an antibody bound to a target antigen for it to be protective.…”
Section: Articlesupporting
confidence: 91%
“…Studies carried out to date using pathogen-derived and modified OMV vaccine formulations show that they are effective at inducing protective systemic and mucosal antigen-specific antibody and T-cell responses. Of interest, Schager et al [ 52 ] have recently shown that administration of OMVs produced by hyperblebbing strains of Salmonella Typhimurium can generate protective antibodies in mice. OMVs produced by different bacteria are equipped with specific sets of proteins that can bind to receptors on host intestinal antigen sampling M cells and DCs.…”
Section: Omv-based Vaccinesmentioning
confidence: 99%
“…Unlike OAg-CRM197 glycoconjugates, in which variable amounts of high-, mixed-and low-molecular weight O-antigens can be present, the GMMA OAg population is mainly composed of highly glycosylated mixed-molecular weight molecules, 170,172 which have been associated with high immunogenicity. 148 Together with the possibility of inducing an immune response against surface components other than the OAg (such as porins), 173 these features may account for the enhanced immunogenicity and efficacy of GMMA vaccines in comparison with the OAg-CRM197 formulations. Schager and colleagues 173 showed that the protection conferred by iNTS GMMA could be achieved even in the absence of OAg, was predominantly B cell-dependent, and was long-standing, thereby further highlighting the potential of GMMA as an iNTS vaccine candidate.…”
Section: Generalized Modules For Membrane Antigens (Gmma) Vaccinesmentioning
confidence: 99%
“…148 Together with the possibility of inducing an immune response against surface components other than the OAg (such as porins), 173 these features may account for the enhanced immunogenicity and efficacy of GMMA vaccines in comparison with the OAg-CRM197 formulations. Schager and colleagues 173 showed that the protection conferred by iNTS GMMA could be achieved even in the absence of OAg, was predominantly B cell-dependent, and was long-standing, thereby further highlighting the potential of GMMA as an iNTS vaccine candidate. The power of this formulation is exemplified by the success of the GMMA-based Shigella sonnei vaccine, which is currently in clinical phase 2 and has yielded promising immunogenicity and safety data.…”
Section: Generalized Modules For Membrane Antigens (Gmma) Vaccinesmentioning
confidence: 99%